2020
DOI: 10.3390/genes11121424
|View full text |Cite
|
Sign up to set email alerts
|

HOG-Independent Osmoprotection by Erythritol in Yeast Yarrowia lipolytica

Abstract: Erythritol is a polyol produced by Yarrowia lipolytica under hyperosmotic stress. In this study, the osmo-sensitive strain Y. lipolytica yl-hog1Δ was subjected to stress, triggered by a high concentration of carbon sources. The strain thrived on 0.75 M erythritol medium, while the same concentrations of glucose and glycerol proved to be lethal. The addition of 0.1 M erythritol to the medium containing 0.75 M glucose or glycerol allowed the growth of yl-hog1Δ. Supplementation with other potential osmolytes such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The yeast Y. lipolytica is able to synthesize erythritol from glycerol, as a response to high osmotic stress [4]. It was shown that the last step of the erythritol synthesis pathway is reduction of d-erythrose to erythritol (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast Y. lipolytica is able to synthesize erythritol from glycerol, as a response to high osmotic stress [4]. It was shown that the last step of the erythritol synthesis pathway is reduction of d-erythrose to erythritol (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Erythritol is a four-carbon polyol that can be found in fruits, such as pears, grapes or melon, where it acts as a carbon store, while many microorganisms produce erythritol under high osmotic pressure as an osmoprotectant [4]. It is characterized by stability at high temperatures and over a wide range of pH [5].…”
Section: Introductionmentioning
confidence: 99%
“…yeasts, such as Zygosaccharomyces, Debaryomyces, Hansenula, Pichia, can grow under high osmotic pressure (high sugar content or salinity) (Brown, 1978). These hyperosmolar yeasts can stimulate an osmotic response mechanism in a hyperosmolar environment, that is, accumulate one or more compatible solutes for resistance to hyperosmolar environment (Rzechonek et al, 2020;Libo, 2015). Glycerol is the most common osmoprotective agent in yeast, but sugar alcohols such as erythritol, D-arabitol and mannitol also have similar functions (Rzechonek et al, 2020;Libo, 2015).…”
Section: Manymentioning
confidence: 99%
“…Erythritol is a four-carbon polyol found in fruit such as pears, grapes or melons where it acts as a carbon store. Many microorganisms produce erythritol under high osmotic pressure as an osmoprotectant [4]. It is characterized by stability at high temperatures and over a wide range of pH values [5].…”
Section: Introductionmentioning
confidence: 99%
“…The yeast Y. lipolytica is able to synthesize erythritol from glycerol as a response to high osmotic stress [4]. It was shown that the last step of the erythritol synthesis pathway is the reduction of d-erythrose to erythritol (Figure 1).…”
Section: Introductionmentioning
confidence: 99%